Preparation, characterization, and food application of rosemary extract-loaded antimicrobial nanoparticle dispersions. (March 2019) - Lee, Kyung Hyun; Lee, Ji-Soo; Kim, Eun Suh; Lee, Hyeon Gyu
Abstract: Rosemary extract (RE) was nanoencapsulated with the natural antimicrobial polysaccharide chitosan and γ-poly glutamic acid (γ-PGA) to improve the antimicrobial activity of RE. Three types of RE nanoparticles (RENPs) were generated with different chitosan concentrations (0.1–1.8 mg/mL) and particle sizes (200–600 nm). Nanoencapsulation significantly increased the antimicrobial activity of RE against Bacillus subtilis, and the highest activity was observed for the largest particles, which were prepared with the highest chitosan concentration. Interestingly, the antimicrobial activity of the RE nanoparticle dispersions (RENPDs), the mixture of RENPs and free RE was significantly higher than those of free RE and RENPs, despite the same RE concentration. When the RENPDs were applied to barley tea, all types of RENPDs exhibited significantly higher antimicrobial activity than free RE, reducing the population of Bacillus subtilis by more than 0.5–3.6 log CFU/mL. Therefore, this study suggests the potential of not only RE-loaded chitosan/γ-PGA NPs but also NPDs as a natural preservative in food. Graphical abstract: Highlights: Rosemary extract (RE) was nanoencapsulated with chitosan (CS) to improve antimicrobial activity. Blank CS nanoparticles (NPs) without any core material had antimicrobial activity. CS synergistically enhanced the antimicrobial activities of the encapsulated RE. RE NP dispersions (NPDs) had significantly higher antimicrobial activity than free RE and RE NPs.